2019
DOI: 10.1113/jp277833
|View full text |Cite
|
Sign up to set email alerts
|

A molecular rheostat: Kv2.1 currents maintain or suppress repetitive firing in motoneurons

Abstract: Key points Kv2 currents maintain and regulate motoneuron (MN) repetitive firing properties. Kv2.1 channel clustering properties are dynamic and respond to both high and low activity conditions. The enzyme calcineurin regulates Kv2.1 ion channel declustering. In patholophysiological conditions of high activity, Kv2.1 channels homeostatically reduce MN repetitive firing. Modulation of Kv2.1 channel kinetics and clustering allows these channels to act in a variable way across a spectrum of MN activity states. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(65 citation statements)
references
References 75 publications
2
63
0
Order By: Relevance
“…One stimulus that results in dephosphorylation of Kv2.1 and dispersal of Kv2.1 clusters in CHNs is acute elevation in intracellular Ca 2+ in response to treatment with the excitatory neurotransmitter glutamate (Misonou et al, 2004; Misonou et al, 2006). In contrast, suppression of neuronal activity with tetrodotoxin (TTX) causes an increase in Kv2.1 phosphorylation and clustering (Cerda and Trimmer, 2011; Romer et al, 2019). We found that glutamate stimulation of CHNs not only reduced Kv2.1 clustering, but also significantly decreased the colocalization between Cav1.2 and RyRs, decreased the size of somatic RyR clusters, and increased the distance between somatic Cav1.2 clusters (Figure 1J–N).…”
Section: Resultsmentioning
confidence: 99%
“…One stimulus that results in dephosphorylation of Kv2.1 and dispersal of Kv2.1 clusters in CHNs is acute elevation in intracellular Ca 2+ in response to treatment with the excitatory neurotransmitter glutamate (Misonou et al, 2004; Misonou et al, 2006). In contrast, suppression of neuronal activity with tetrodotoxin (TTX) causes an increase in Kv2.1 phosphorylation and clustering (Cerda and Trimmer, 2011; Romer et al, 2019). We found that glutamate stimulation of CHNs not only reduced Kv2.1 clustering, but also significantly decreased the colocalization between Cav1.2 and RyRs, decreased the size of somatic RyR clusters, and increased the distance between somatic Cav1.2 clusters (Figure 1J–N).…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between Kv2 channels and VAPs seems to be an important determinant in the localization of these proteins in neurons with overexpression of Kv2.1 causing VAPs to redistribute to large ER-PM clusters while loss of VAPs reduce Kv2 clustering in the PM (Johnson et al, 2018; Kirmiz et al, 2018). Kv2 clusters in motor neurons can also be seen to be dynamic, redistributing into smaller clusters following neuronal activity (Romer et al, 2019).…”
Section: Er-plasma Membrane Contacts In Neuronsmentioning
confidence: 99%
“…Previous studies suggested that Kv2.1 channels regulate repetitive firing. For example, in layer 3 pyramidal cells and spinal motoneurons, Kv2.1 currents facilitate repetitive firing by preventing Na + channel inactivation (Guan et al, 2013;Romer et al, 2019). The FS phenotype of PV neurons, however, differs significantly from the firing patterns of pyramidal cells or motoneurons.…”
Section: Kv21 Deficiency Alters Repetitive Firing In a Computationalmentioning
confidence: 99%
“…Next, we used the FS cell model to examine whether the strong stuttering phenotype produced by reduced levels of Kv2.1 conductance is associated with increased Na + channel inactivation, since Kv2.1 current was reported to facilitate repetitive firing by reducing Na + channel inactivation in other types of neurons (Guan et al, 2013;Romer et al, 2019). We Figure 5E).…”
Section: Kv21 Deficiency Alters Repetitive Firing In a Computationalmentioning
confidence: 99%
See 1 more Smart Citation